Neonatal Resuscitation in Children 2021: Focus on Training, Technology, and New Clinical Approaches - Daniele Trevisanuto; Viraraghavan Vadakkencherry Ramaswamy; Paolo Ernesto Villani (MDPI AG, 2022)
Neonatal resuscitation remains a hot topic for pediatricians and neonatologists worldwide [...]